Redesign of a 60,000 DWT Dry Bulk Jetty from Precast to Cast-In-Situ System in a Seismic Port Area: Structural Design and Cost Implication. - Yudoprasetyo, Kohar; Kesuma, Gandhi; Affandhie, Raden Buyung Anugraha (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study presents the redesign and structural verification of a 60,000 DWT dry bulk jetty in the coastal area of Gresik, East Java, where the project site is characterized by soft ground (Site Class SE) and requires earthquake-resistant performance. The original structural concept is reconfigured from a precast system to a cast-in-situ reinforced concrete system to improve continuity, connection robustness, and constructability in a seismic port environment. A three-dimensional numerical model was developed in SAP2000 to represent the interaction between deck slab, beams, pile caps, and steel pipe piles (SPP Ø1016 mm, t = 15.9 mm). Design actions include dead and operational live loads (3.0 t/m²), crane wheel loads under critical transverse positions, vessel berthing and mooring loads (fender reaction and bollard demand), and response-spectrum earthquake loading based on Indonesian provisions. The redesigned superstructure adopts a 350 mm deck slab with D16–150 reinforcement, and beam detailing is provided for longitudinal, transverse, and crane beams. Foundation checks confirm that axial reactions remain below the pile bearing capacity, pile utilization ratios are below unity, maximum vertical settlement is 0.63 cm (within the allowable limit), and maximum lateral deflection is 85.14 mm (below the serviceability threshold). The lump-sum construction cost implication for the redesigned system is USD 11.062 million.